Structural Models of Customer Loyalty on Star Hotel in Medan, Indonesia - Dedek Kurniawan Gultom; Nadia Ika Purnama; Muhammad Arif (University of Merdeka Malang, 2021)
This study aims to analyze directly and indirectly the service quality and hotel image on consumer satisfaction and customer loyalty. The location of this study is in several star hotels in Medan such as Graha Serela, Santika Premier Dyandra, Polonia, Grand Swiss-Bell, JW Marriot, Garuda Plaza, and Grand Aston City Hall Hotel. Populations in this study are guests who staying at a Starred Hotel in Medan in 2019, while the sample is determined as many as 215 consumers (hotel guests). Data answering techniques used are interviews, questionnaires and documentation studies. The data analysis method used in this study is Structural Equation Modelling (SEM). The results of research show directly, the quality of service provided to Consumer Satisfaction, Service Quality affect on Customer Loyalty, Hotel Image against Consumer Satisfaction, Hotel Image affect Customer Loyalty and Consumer Satisfaction against Customer Loyalty. Directly, the service quality and hotel image of customer loyalty through customer satisfaction.